The Entrepreneur: Who Is He ? / L'entrepreneur: Qui est-il ? - Massey, Ralph (Relations industrielles / Industrial Relations, 1954)
SummarySince the end of the Eighteenth Century, some economists and economic historians have given a particular attention to the functions of the entrepreneur. But actually who is the entrepreneur in Canada? Has the entrepreneurial function changed with the evolution of the economy ? Having examined those various opinions, the author gives his own notion of the "entrepreneur" and leaves to the reader a few unanswered questions important for developed or underdeveloped countries seeking to maintain or promote their wellbeing.